Computing Edge Version of Resolvability and Double Resolvability of a Graph - Muhammad Ahmad; Zohaib Zahid; Tabasam Rashid; Juan Luis Garcia Guirao (Journal of Chemistry)
The field of graph theory is extensively used to investigate structure models in biology, computer programming, chemistry, and combinatorial optimization. In order to work with the chemical structure, chemists require a mathematical form of the compound. The chemical structure can be depicted using nodes (which represent the atom) and links (which represent the many types of bonds). As a result, a graph theoretic explanation of this problem is to give representations for the nodes of a graph such that different nodes have unique representations. This graph theoretic study is referred to as the metric dimension. In this article, we have computed the edge version of the metric dimension and doubly resolving sets for the family of cycle with chord Cnt for n≥6 and 2≤t≤⌊n/2⌋.